2013
DOI: 10.1002/jsfa.6473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flavonoids on learning, memory and neurocognitive performance: relevance and potential implications for Alzheimer's disease pathophysiology

Abstract: Recent evidence has indicated that a group of plant-derived compounds known as flavonoids may exert particularly powerful actions on mammalian cognition and may reverse age-related declines in memory and learning. In addition, growing evidence is also suggestive that flavonoids may delay the development of Alzheimer's disease-like pathology, suggestive of potential dietary strategies in dementia. Although these low-molecular-weight phytochemicals are absorbed to only a limited degree, they have been found to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 202 publications
2
71
0
1
Order By: Relevance
“…Research has indicated that phytochemicalrich foods, particularly those rich in flavonoids, may exert especially powerful effects on cognitive functions (Vauzour, 2014). Flavonoids have a number of effects on the brain, including a potential of protection of neurons against injuries induced by neurotoxins and promotion of learning and memory (Spencer, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has indicated that phytochemicalrich foods, particularly those rich in flavonoids, may exert especially powerful effects on cognitive functions (Vauzour, 2014). Flavonoids have a number of effects on the brain, including a potential of protection of neurons against injuries induced by neurotoxins and promotion of learning and memory (Spencer, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, growing research has focused on the potential of dietary flavonoids in reducing the risk of AD and other dementing disorders (Vauzour, 2014). Research shows the connection between normal ageing and neurodegenerative diseases such as AD with oxidative stress and inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last years, efforts have been made at investigating the effect polyphenols on neuroinflammation. Although not exhaustive, the main antiinflammatory properties of polyphenols may be summarised by (1) a capacity to downregulate the activity of proinflammatory transcription factors such as NF-kB, Nrf2 or STAT through their influences on a number of glial and neuronal signalling pathways, (2) an inhibitory role on the release of cytokines, such as interleukin IL-1b and TNF-a, from primed microglia, (3) an inhibitory action against the production of NO and PGE2 in response to microglia activation, (4) an ability to inhibit the activation of NADPH oxidase and subsequent ROS generation in activated glia, and (5) an inhibitory action against microglia priming through toll-like receptors (TLR) activation (Gonzalez-Gallego et al, 2010;Vauzour, 2014). For example, fisetin (0.05%, 6 months) reduced the protein expression of inflammatory markers in huAPPswe/PS1DE9 transgenic mice in an ERK-p25-mediated pathway without affecting the mRNA expression of NF-kB1 (Currais et al, 2014).…”
Section: Polyphenols Mitigate Neuroinflammationmentioning
confidence: 99%
“…The use of flavonoids as therapeutic compounds has also been suggested in learning, memory, neurocognitive performances and Alzheimer's disease [147,148] . Recently the beneficial effects of flavanoids have been showed for the alzheimer's pathology in animal and in vitro experimental model [149][150][151][152] .…”
Section: Evidences For the Beneficial Use Of Antioxidants In Neurodegmentioning
confidence: 99%